Determining the threshold for variation in indoor temperature reduction capacity of green roofs with different depths in hot and dry climates - Muhammad Salihu, Murtala; Awad Abuhussain, Mohammed; Mohammed Elhassan, Zeinab Abdallah; Ramadan Abdelhai , Nada Mohamed (Cadernos de Educação Tecnologia e Sociedade, 2024)
To forestall the dangers of overdesign, initial and maintenance costs, and unnecessary loading on the supporting roof, the study was primarily aimed at determining the significant difference in indoor temperature reduction capacity between various green roof models of varying thicknesses within the extensive green roof category. Using a contextualized substrate layer of 25mm as the difference in depth between green roof alternatives, the degree of thermal insulation for the interior was observed on six extensive green roof models of 50mm, 75mm, 100mm, 125mm, and 150mm thicknesses. This is to elucidate the level of significant differences in thermal efficiency between the models. EnergyPlus 8.3.0 simulation software was used to conduct a thermal performance survey on the sampled models. The temperature profiles of all the cases were collected and subjected to statistical analysis using SPSS V 21.0 to conduct an ANOVA and a proceeding Post hoc test to determine where the difference lies between the green roof groups. The results revealed that; no substantial difference in thermal performance exists between alternatives where the difference in depth is around the 25mm mark. Revealing that the threshold for any significant change in thermal insulation is denoted by a 50mm difference between alternatives. This research was carried out to facilitate the initial process of green roof selection, design, detailing, and specifications writing for architect engineers, and other stakeholders.